2015
DOI: 10.1007/s00056-015-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different orthodontic primers on enamel demineralization around orthodontic brackets

Abstract: Filled sealants may not have a protective effect against enamel demineralization. Transbond Plus Self-Etching Primer should be used cautiously, considering the risk of demineralization involved in its application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The SEM images indicated more surface irregularities with TE than with SE, which supports the findings in the literature on shallower irregularities and less enamel dissolution with SE ( Hashimoto et al, 2013 , Horiuchi et al, 2009 ). The surface roughness findings and reduced invasiveness of the FF adhesive and SE could be related to the less resin removal with the FF system, whereas the weaker etching composition of SE might have resulted in a less distinct surface, reduced resin penetration, and less removal need of the remnants ( Baysal et al, 2015 , Visel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…The SEM images indicated more surface irregularities with TE than with SE, which supports the findings in the literature on shallower irregularities and less enamel dissolution with SE ( Hashimoto et al, 2013 , Horiuchi et al, 2009 ). The surface roughness findings and reduced invasiveness of the FF adhesive and SE could be related to the less resin removal with the FF system, whereas the weaker etching composition of SE might have resulted in a less distinct surface, reduced resin penetration, and less removal need of the remnants ( Baysal et al, 2015 , Visel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, practitioners had to be vigilant in removing any excess to prevent plaque retention, gingival irritation, and white spots [ 13 , 14 , 15 ]. FF adhesives use a low-viscosity adhesive that is applied to a non-woven material made of polypropylene fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In their study in which the demineralization around brackets bonded to cattle teeth was investigated, Baysal et al (28) formed and compared groups as Transbond XT adhesive primer used on acid etched surfaces, Pro Seal adhesive primer, Opal Seal adhesive primer, and Transbond Plus SEP used on the non-etched surface. They reported that in demineralization values between the T0 and T1 measurements was observed to be the highest on the gingival surface adjacent to the bracket in all groups, regardless of the enamel surface conditioning method that was applied.…”
Section: Discussionmentioning
confidence: 99%